2020
DOI: 10.21273/horttech04464-19
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Sweetgale, Rhodora, and Catberry by Stem Cuttings

Abstract: Sweetgale (Myrica gale), rhodora (Rhododendron canadense), and catberry (Ilex mucronata) are shrubs of eastern North America that may have potential for broader use in horticultural landscapes. Because information on their vegetative propagation is scarce, we conducted experiments over 2 years to evaluate the effects of cutting collection date, wounding, substrate composition, and the concentration of applied potassium sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Esta investigación muestra que la mezcla de sustrato peat-moss y agrolita puede ser usado exitosamente para enraizar esquejes de H. macrophylla, lo cual también ha sido reportado para otras especies. Peterson et al (2019) concluyeron que el uso de peat-moss en la producción de esquejes de plantas semileñosas, después de 120 días de establecidas, produjeron plantas completas, con buenas raíces y entre tres y seis brotes basales. Por otra parte Moreno et al ( 2009) evaluaron la propagación asexual de Uchuva (Physalis peruviana L.) en diferentes sustratos y encontraron que peat-moss, permitió mayor porcentaje de enraizamiento y producción de hojas, como consecuencia de una buena formación de raíces.…”
Section: Discussionunclassified
“…Esta investigación muestra que la mezcla de sustrato peat-moss y agrolita puede ser usado exitosamente para enraizar esquejes de H. macrophylla, lo cual también ha sido reportado para otras especies. Peterson et al (2019) concluyeron que el uso de peat-moss en la producción de esquejes de plantas semileñosas, después de 120 días de establecidas, produjeron plantas completas, con buenas raíces y entre tres y seis brotes basales. Por otra parte Moreno et al ( 2009) evaluaron la propagación asexual de Uchuva (Physalis peruviana L.) en diferentes sustratos y encontraron que peat-moss, permitió mayor porcentaje de enraizamiento y producción de hojas, como consecuencia de una buena formación de raíces.…”
Section: Discussionunclassified
“…Ferus et al (2017) reported that the rooting efficiencies of cuttings ranged between 0% and 100% in their study with eight Rhododendron species. Peterson et al (2020) conducted a study on the propagation of sweetgale, rhodora, and catberry species by cuttings. They found that the K-IBA concentration and wounding treatments in Rhodora (Rhododendron canadense (L.) Torr.)…”
Section: R Caucasicum Pallasmentioning
confidence: 99%